PERTANGGUNGJAWABAN PIDANA PIHAK LEASING YANG MEMPEKERJAKAN DEBT COLLECTOR DALAM MENYELESAIKAN PIUTANG DENGAN MELAKUKAN PENGANIAYAAN DI KEPOLISIAN RESORT KOTA PEKANBARU - Habib, Ikhwan; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Some actions of debt collectors even lead to criminal action. For example, debt collectors who act forcibly seized goods, making a scene, terrorizing either directly or phone, even threatened to kill customers and that just happened, killed his case Uniting Nations Party Secretary